1991
DOI: 10.1002/stem.5530090203
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of nuclear Proto‐Oncogene expression by Erythropoietin (Epo) in Epo‐responsive murine cell lines

Abstract: The signal transduction system of erythropoietin (Epo) and the accompanying molecular control mechanism of proliferation and differentiation of erythroid progenitors remains largely unknown. In this study, the effect of Epo on the expression of nuclear oncogenes was investigated in two murine cell lines which respond to the hormone in different ways: ELM-I-1 cells proliferate independently of Epo, but differentiate in response to the hormone, while the growth of DA-1ER cells is absolutely dependent on Epo or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…This finding regarding c-fos and c-jun contrasts with several reports that EPO induces mRNA for c-fos in erythroleukemia cell lines or primary isolates of human erythroid progenitors (Tsuda et al, 1991;Umemura et al, 1988) or that the c-fos gene is constitutively expressed in early and late erythroblasts (Caubet et al, 1989). While it is possible that there are different responses in the experimental cell systems used by various investigators, our results show that mRNAs for c-fos and c-jun are transiently induced in FVA cells by equilibration in basal medium without growth factors, and such effects could occur during other cell handling procedures.…”
Section: Discussioncontrasting
confidence: 66%
“…This finding regarding c-fos and c-jun contrasts with several reports that EPO induces mRNA for c-fos in erythroleukemia cell lines or primary isolates of human erythroid progenitors (Tsuda et al, 1991;Umemura et al, 1988) or that the c-fos gene is constitutively expressed in early and late erythroblasts (Caubet et al, 1989). While it is possible that there are different responses in the experimental cell systems used by various investigators, our results show that mRNAs for c-fos and c-jun are transiently induced in FVA cells by equilibration in basal medium without growth factors, and such effects could occur during other cell handling procedures.…”
Section: Discussioncontrasting
confidence: 66%
“…Epo up-regulation of c-fos was demonstrated several years ago in ELM-1-1 cells (30). This action of Epo on Epo-dependent cells was confirmed by Miura et al (51) who demonstrated an up-regulation of c-fos, c-myc, and egr1.…”
Section: Discussionmentioning
confidence: 67%
“…However, other investigators used an Epo-sensitive cell line and demonstrated that, in contrast to the effect of Me 2 SO on c-myc, Epo treatment up-regulated expression of the proto-oncogene concomitant with induction of differentiation (29). Although up-regulation of c-myc by Epo was not detected in studies of Epo-sensitive ELM-1-1 cells (30), it was detected in a novel J2E cell line (31) and was later shown also in erythroid cells derived from the spleens of Friend virus-infected mice (32).…”
Section: Discussionmentioning
confidence: 97%
“…Spangler et al (1991Spangler et al ( , 1992 presented evidence suggesting that the increase in c-myc mRNA is dependent on the activation of protein kinase C. Also, in these erythroleukemic cell lines a decrease in mRNA for the c-myb gene occurs following EPO administration (Todokoro et al, 1988;Spangler et al, 1991). A report of increased c-fos gene expression within 30 min of EPO exposure in murine erythroleukemia cell lines is of uncertain significance since this study involved the uncontrolled replenishment of fresh medium and serum to starved cells at the same time as exposure to EPO (Tsuda et al, 1991).…”
Section: Cellular Responses To Epo Stimulation and The Nature Of Epo mentioning
confidence: 99%